Transthyretin: roles in the nervous system beyond thyroxine and retinol transport. Issue 2 (March 2012) - Oliveira, Sandra Marisa; Cardoso, Isabel; Saraiva, Maria João
Transthyretin (TTR) is a plasma- and cerebrospinal fluid-circulating protein. Besides the primordially attributed systemic role as a transporter molecule of thyroxine (T4 ) and retinol (through the binding to retinol-binding protein [RBP]), TTR has been recognized as a protein with important functions in several aspects of the nervous system physiology. TTR has been shown to play an important role in behavior, cognition, amidated neuropeptide processing and nerve regeneration. Furthermore, it has been proposed that TTR is neuroprotective in Alzheimer''s disease and cerebral ischemia. Mutations in TTR are a well-known cause of familial amyloidotic polyneuropathy, an autosomal dominant neurodegenerative disorder characterized by systemic deposition of TTR amyloid fibrils, particularly in the peripheral nervous system. The purpose of this review is to highlight the roles of TTR in the nervous system, beyond its systemic role as a transporter molecule of T4 and RBP–retinol.